82.2k views
2 votes
X - 2y =0

3x + y = 0
solve using the substitution method
to solve the linear system


User Curiousity
by
5.5k points

1 Answer

0 votes

Answer:

x=0, y=0

Explanation:

① Label the 2 given equations.

x -2y= 0 -----(1)

3x +y= 0 -----(2)

② Make x the subject of formula in equation (1).

From (1): x= 2y -----(3)

③ Substitute equation (3) into (2):

3(2y) +y= 0

Expand:

6y +y= 0

Simplify:

7y= 0

y= 0

④ Find x.

Subst. y=0 into (3):

x= 2(0)

x= 0

User Henrik Peinar
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.